Across the sea to Ireland: Return Atlantic migration before the First World War - Alan Fernihough; Cormac Ó Gráda (University College Dublin, UCD Centre for Economic Research, 2019)
Are return migrants 'losers' who fail to adapt to the challenges of the host economy, and thereby exacerbate the brain drain linked to emigration? Or are they 'winners' whose return enhances the human and physical capital of the home country? These questions are the subject of a burgeoning literature. This paper analyze a new database culled from the 1911 Irish population census to address these issues for returnees to Ireland from North America more than a century ago. The evidence suggests that those who returned had the edge over the population as a whole in terms of human capital, if not also over those who remained abroad.
Keywords: N33; J61; 330; migration; brain gain; economic history; Ireland